The analysis of traffic accidents on Lithuanian regional gravel roads - Mamčic, Stanislav; Sivilevičius, Henrikas (Transport, 2013)
A great number of serious road accidents occur all over the world every year. In spite of some progress in this area, road traffic safety has remained an acute problem in recent years. Traffic accidents on the road depend on the following factors: road traffic volume, road traffic speed, road condition, weather conditions for traffic, driving experience and driving culture. All these factors are related to traffic safety, human lives and health. The main goal of this work is to provide a statistical analysis of traffic accidents and investigate the causes, structure, dynamics and seasonal character of traffic accidents on Lithuanian regional gravel roads. It has been established that seasons play an important role for traffic accidents on regional gravel roads in Lithuania. Rates for traffic accidents increase from spring to autumn. The number of traffic accidents on Lithuanian roads decreased considerably in 2008 and 2009. First Published Online: 03 Apr 2013